Improving Narrative Writing Skills with the CTL Approach and Illustrated Image at SMA Negeri 5 Semarang - Nisa, Wari’atun; Widarti Lestari, Maria Yosephin; Ekowati, Windy (Pascasarjana Universitas PGRI Semarang, 2023)
Writing is a language skill with the highest difficulty level compared to other language skills. Writing skills at SMA Negeri 5 Semarang based on the results of interviews conducted by researchers with English teachers of class X and the results of the initial survey test found a problem, namely the low ability to write stories in English subjects. They don't have self-confidence, are afraid of making mistakes, and don't know what to write and how to start. For this reason, the teacher conducts Classroom Action Research by applying a contextual approach (Contextual Teaching and Learning (CTL)) and illustrated media for Class X Students of SMA Negeri 5 Semarang. The common goal of learning writing skills is for students to express ideas, ideas, opinions, and knowledge systematically and in writing and have a penchant for writing